Mongolia : 2017 Article IV Consultation and Request for an Extended Arrangement Under the Extended Fund Facility-Press Release: Staff Report; and Statement by the Executive Director for Mongolia. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights Mongolia's promising longer-term prospects given its abundant natural resources. In recent years, however, the economy has faced substantial challenges, as external shocks and expansionary fiscal and monetary policies have compounded structural weaknesses. Mongolia remains heavily exposed to external shocks, given its export profile, and a key challenge will be to avoid the boom-bust cycles of the past. The discussions with authorities have focused on improving the fiscal framework and strengthening policy discipline, complemented by structural reforms to boost diversification and competitiveness and by efforts to strengthen and better target the social safety net.